Better bullets to shoot small mammals without poisoning scavengers. (28th September 2017) - McTee, Michael; Young, Matt; Umansky, Andre; Ramsey, Philip
ABSTRACT: Recreational shooters kill millions of small mammals each year and scavengers that ingest the carcasses can be poisoned if lead bullets are used. Less toxic bullets exist, but their performance and potential risk to deposit lead in carcasses is understudied. In May 2016, shooters controlled populations of Columbian ground squirrels ( Urocitellus columbianus ) at ranches in Idaho and Montana, USA, by shooting them with .17 HMR (Hornady Magnum Rimfire), .22 LR (long rifle), and .223 Rem (Remington) rifles with expanding and nonexpanding lead and nonlead bullets. We recorded whether bullets instantly incapacitated ground squirrels and then counted the number of bullet fragments in each carcass to estimate concentrations of residual lead. All types of lead bullets left lead in at least one‐third of the Columbian ground squirrels. Unexpectedly, estimated concentrations of lead in carcasses did not differ between expanding and nonexpanding bullets within the .17 HMR and .22 LR calibers, partially because of the high variability in fragmentation. The greatest estimated concentrations of lead were in Columbian ground squirrels shot with expanding ammunition in .17 HMR and .223 Rem, which had an average of 23.6 mg and 91.2 mg Pb/carcass, respectively. Nonlead bullets incapacitated similar to lead bullets. Our results indicate that nonlead bullets eliminate the risk of additional lead exposure to scavengers while maintaining the lethality of lead bullets. © 2017 The Wildlife Society. Abstract : Recreational shooters kill millions of small mammals each year and scavengers that ingest the carcasses can be poisoned if lead bullets are used. Our results indicate that nonlead bullets eliminate the risk of additional lead exposure to scavengers while maintaining the lethality of lead bullets when shooting Columbian ground squirrels ( Urocitellus columbianus ).